2018
DOI: 10.1038/s41598-018-35853-y
|View full text |Cite
|
Sign up to set email alerts
|

Parent-embryo acoustic communication: a specialised heat vocalisation allowing embryonic eavesdropping

Abstract: Sound is arguably the external cue most accessible to embryos of many species, and as such may constitute an unrivalled source of early information. Recent evidence shows that prenatal sounds, similarly to maternal effects, may shape developmental trajectories. Establishing whether parental vocalisations are signals directed at embryos, or parental cues on which embryos eavesdrop, can elucidate whether parents or embryos control developmental outcomes. Prenatal exposure to a characteristic heat-related parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…redness of highly vascularised skin patch), that were primarily associated with a thermoregulation function, have then evolved to become visual signals during social displays in some species 53 – 55 . In our study, consistent with previous findings in wild and captive zebra finches 26 , 27 , we showed that heat-calls, starting at T a ~ 41 °C and T b ~ 43 °C, can reliably signal hot environmental conditions and the emitter’s hyperthermic state to embryos (or possibly to conspecifics). Therefore, it is plausible that heat-calls could have evolved from a cue initially associated with a thermoregulatory mechanism into a signal directed at embryos, which increases offspring fitness.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…redness of highly vascularised skin patch), that were primarily associated with a thermoregulation function, have then evolved to become visual signals during social displays in some species 53 – 55 . In our study, consistent with previous findings in wild and captive zebra finches 26 , 27 , we showed that heat-calls, starting at T a ~ 41 °C and T b ~ 43 °C, can reliably signal hot environmental conditions and the emitter’s hyperthermic state to embryos (or possibly to conspecifics). Therefore, it is plausible that heat-calls could have evolved from a cue initially associated with a thermoregulatory mechanism into a signal directed at embryos, which increases offspring fitness.…”
Section: Discussionsupporting
confidence: 92%
“…Audio recordings were analysed visually and audibly in Adobe Audition CC (Creative Cloud 2018) by two researchers who were blind to the respirometry values, behavioural data and air temperatures. The onset of calling corresponded to the time when the bird initiated the first heat-call sequence; and the duration of each sequence was noted as previously described 27 . We calculated the proportion of time spent vocal panting over each T a stage and for the total trial duration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal acoustic information has now been shown to directly and adaptively program individual phenotypes for predicted postnatal environments [7,8]. Far from being passive entities isolated from the external world, it is becoming apparent that embryos survey and respond to their environment so as to direct their development [9,10].…”
mentioning
confidence: 99%
“…The parent may modify its incubating behavior according to the development of the egg embryo. Several studies have documented parentembryo communication in birds (Colombelli-Négrel et al 2012;Mariette and Buhanan 2016;Katsis et al 2018;Mariette et al 2018). It is possible that A. superciliaris parents can either perceive the progress of embryo development or communicate with the embryo to achieve synchronism.…”
mentioning
confidence: 99%